THE EFFECT OF REINFORCEMENT ON STUDENTS' LEARNING ACHIEVEMENT IN THE FIELD OF ISLAMIC STUDIES AT SMP NEGERI 34 MAKASSAR - M. Makbul; Ferianto Ferianto (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
This article discusses the Effect of Reinforcement on Students' Learning Achievement in the Field of Islamic Studies at SMP Negeri 34 Makassar". The main issues that will be discussed in this thesis are: 1) How is the application of reinforcement in the field of PAI studies at SMP Negeri 34 Makassar. 2) How is the learning achievement of students in the field of PAI studies at SMP Negeri 34 Makassar. 3) Are there any a significant effect of providing reinforcement on student learning achievement in the field of Islamic studies at SMP Negeri 34 Makassar. The purpose of this study was to determine whether the provision of reinforcement has an influence on the learning achievement of students in the field of Islamic studies at SMP Negeri 34 Makassar. The type of research is quantitative, the data is in the form of numbers and uses statistical analysis. The population in this study were students of class VIII SMP Negeri 34 Makassar, amounting to 259 people. While the sample is class VIIIC, VIIIE, and VIII, namely 92 people with a sampling technique using purposive random sampling. Based on the results of the analysis obtained, namely in the regression equation, it is known that if the value of X is increased, then the value of Y will also increase or in other words that X is directly proportional to Y. It means that the higher the reinforcement that students have, the learning outcomes will also increase. more increasing. Furthermore, it is also obtained Fcount Ftable or 106.91 3.10 then Ha is accepted and H0 is rejected. This means that there is a significant influence between the provision of reinforcement on the learning achievement of class VIII students of SMP Negeri 34 Makassar